Drug utilization research: a review - Meena, Dinesh Kumar; Jayanthi, M. (International Journal of Basic & Clinical Pharmacology, 2019)
Data from drug utilization research is an invaluable resource for all stake holders involved in drug and health policies. Drug utilization is “marketing, distribution, prescription and use of drugs in a society, with special emphasis on the resulting medical, social and economic consequences”. Research on drug utilization includes factors related to prescribing, dispensing, administering and intake of medication and its associated events. The ultimate purpose of drug utilization research is to estimate the optimal quality of drug therapy by identifying, documenting, analysing problems in drug utilization and monitoring the consequences. It encourages the prescribers to prescribe correct drug at appropriate dose and affordable price. It contributes to the knowledge of rational use of drugs in the society; whether the drug is being prescribed appropriately, whether the drug is taken in correct dosage, whether the drug is available at affordable price or misused. It provides valuable feedback about the rationality of the prescription to the doctors. It also assesses whether an intervention affects the drug use in the population by examining the outcomes of different types of intervention given to improve rationality in drug use. Drug utilization research can be qualitative or quantitative and can be done by various methods. This review highlights the understanding of various aspects, different designs and WHO guidelines for conducting drug utilization research.